Increasing the Effectiveness of Public Information on Risk Factors and Self-Control of Hypertensive Disease in Primary Link - Shakhzoda Gulyamova1, Abdigaffar Gadaev2, Rustam Zakirkhodjaev3, Dilmurad Kalandarov4, Dilrabo Sodik (Indian Journal of Forensic Medicine & Toxicology, 2020)
The past 5-year data from 222 randomiy selected outpatient cards of hypertensive patients who werefollowed up at a family polyclinic (n=54) and in a number of rural ambulances (n=168) of the Republik ofUzbekistan were retrospectively analyzed. The physicians from the Tashkent family polyclinic and ruralambulances of a number of the Republic’s regions, who had taken 10-month retraining courses for generalpractitioners, were questioned. Questionnaires were used to study 156 and 119 physicians before and afterretraining, respectively. Two hundred and fifty-six hypertensive patients followed up at the family hospitaland rural ambulances were interviewed using questionnaires and examined. Then some of them (a studygroup) took a course of training at a school for the hypertensive patient and the others (a comparison group)did not participate in the education program. All the patients were followed up for 2 years with a subsequentreexamination and study. Most outpatient cards give recommendations for non-drug treatment incompletely.In a number of cases, the physicians who attach importance to the detection and correction of risk factorshas substantially increased after education. The patients who had taken training courses were found to besignificantly (?<0,001) more aware of their having hypertension and the major risk factors of hypertensivedisease, to be more adherent to treatment, and to know its adequacy.